Political Connection and Creative Accounting on Tax Avoidance - Rahmatia, Adilla; Parwati, Ni Made Suwitri (Accounting Studies and Tax Journal (COUNT), 2024)
This study examines the effect of political connections and creative accounting on tax avoidance. This study employs a quantitative descriptive approach, utilizing a purposive sampling technique for sample selection. Data analysis is conducted using WarpPLS 7.0. The results of this study indicate that political connections and creative accounting significantly positively affect tax avoidance. Policymakers need to increase supervision of politically connected companies to prevent abuse of power, direct further research, and strengthen the role of public accountants in maintaining the integrity of financial statements and compliance with tax regulations.